1998
DOI: 10.1128/jb.180.9.2442-2449.1998
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of an Escherichia coli K-12 Mutant Strain Able To Form Biofilms on Inert Surfaces: Involvement of a New ompR Allele That Increases Curli Expression

Abstract: Classical laboratory strains of Escherichia coli do not spontaneously colonize inert surfaces. However, when maintained in continuous culture for evolution studies or industrial processes, these strains usually generate adherent mutants which form a thick biofilm, visible with the naked eye, on the wall of the culture apparatus. Such a mutant was isolated to identify the genes and morphological structures involved in biofilm formation in the very well characterizedE. coli K-12 context. This mutant acquired the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
242
2
5

Year Published

1999
1999
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 462 publications
(256 citation statements)
references
References 30 publications
7
242
2
5
Order By: Relevance
“…The pta-ackA deletion was moved as described in [11]. The 7.25-kb PvuII fragment containing the csgA-uidA fusion of pOV874 [1] was used to transform the recD csgA D355 strain. White colonies were selected on CFA medium and the fusion was then moved by P1 vir transduction in di¡erent genetic backgrounds.…”
Section: Genetic Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The pta-ackA deletion was moved as described in [11]. The 7.25-kb PvuII fragment containing the csgA-uidA fusion of pOV874 [1] was used to transform the recD csgA D355 strain. White colonies were selected on CFA medium and the fusion was then moved by P1 vir transduction in di¡erent genetic backgrounds.…”
Section: Genetic Methodsmentioning
confidence: 99%
“…Adherence of both E. coli K12 and medical isolates depends on curli production [1]. In order to address the possible regulation of the curli operon by cpxA, we used a csgA: :uidA transcriptional fusion which enables us to estimate the synthesis rate of curlin in di¡erent cpxA backgrounds.…”
Section: Involvement Of Cpxa In Adherence Via Regulation Of Expressiomentioning
confidence: 99%
See 2 more Smart Citations
“…Also, none of the genes selected on the basis of the results of their over-expression caused unusual bio¢lm formation in LB or M63-glucose medium or in the presence of varying concentrations of NaCl (0.1^0.4 M) when deleted in W3110 strain. Although it has been reported that curli production is important for the adherence of bio¢lm-forming cells [35], disruptants of csgF and csgG genes for curli transport and assembly formed bio¢lm. We observed that the strain W3110 we used to construct disruptants was ine⁄cient in curli production, judging from the color of its colonies on Congo red plates (data not shown).…”
Section: Disruption Of Selected Genesmentioning
confidence: 98%